Firm survival in professional sports: Evidence from the German football league - Harald Oberhofer; Tassilo Philippovich; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2010)
This paper investigates firm survival in professional football, arguing that the relegation and promotion system in football leagues is very similar to firm exits and entries in traditional goods and service markets. Empirically, we use a dataset containing information on how long football teams have participated in the German Premier League over the playing seasons 1981-82 to 2009-10. Controlling for club and market specific characteristics, such as a team's budget or its player composition, our findings suggest that younger firms are systematically exposed to higher risks of market exit in professional football, which is often referred to as `liability of newness' in organizational ecology.
Keywords: C41; L21; L25; L83; 330; Firm survival; liability of newness; duration analysis; sports leagues; relegation